Synergizing CNN, DBN-Net, Transfer Learning, and DES: An Efficient Hybrid Framework Over Cardiovascular Disease Prediction - Valasapalli, Mounika; Sai, N. Raghavendra (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cardiovascular diseases (CVDs) continue to be a significant global health challenge, necessitating more accuracy and an early prediction to mitigate their impact. Cardiovascular disease (CVD) remains a global public health concern, accounting for nearly 18 million deaths annually. Timely diagnosis and intervention are paramount for improving CVD outcomes. Machine learning (ML) has emerged as a powerful tool for CVD prediction, but existing ML models often struggle with accuracy and interpretability. This study proposes a novel hybrid framework that integrates convolutional neural networks (CNNs), deep belief networks (DBN-Nets), transfer learning, and dynamic ensemble selection (DES) for CVD prediction. The proposed framework initially leverages CNNs to extract high-level features from electrocardiogram (ECG) signals. Subsequently, DBN-Nets are employed to learn a hierarchical representation of the extracted features, enhancing the model's ability to capture complex patterns in the data. To further augment the model's performance, transfer learning is implemented by fine-tuning a pre-trained DBN-Net on the CVD prediction task. Finally, DES is utilized to select the most informative features, reducing the dimensionality of the data and improving the model's interpretability. Experimental results on a benchmark ECG dataset (PhysioNet ECG Database) demonstrate that the proposed hybrid framework outperforms state-of-the-art methods in terms of accuracy, sensitivity, specificity, and F1-score.This study contributes to the ongoing pursuit of precision medicine and proactive disease management, which enhances survival of many patients with advance prescription alerting.